Craving Mediates the Relation Between Impulsivity and Alcohol Consumption Among University Students. Issue 6 (19th August 2019) - Flaudias, Valentin; Maurage, Pierre; Izaute, Marie; de Chazeron, Ingrid; Brousse, Georges; Chakroun‐Baggioni, Nadia
Abstract : Background and Objectives: The relationship between impulsivity and craving in severe alcohol use disorders is well established, but the presence and characteristics of this link in University students are still to be established. The present study aims to better understand the relationship between impulsivity and craving in university students and to determine the influence of these variables on alcohol consumption characteristics. Methods: A large sample of university students ( N = 1055, mean age: 20.9 years; 713 women) completed an online questionnaire to evaluate alcohol use, impulsivity, and craving. Results: Linear regression analysis demonstrated that the compulsive dimensions of craving ( P < .001), sensation seeking ( P < .001), and lack of premeditation ( P < .001) constitute strong predictors of current consumption. A receiver operating characteristic (ROC) curve analysis determined the threshold level above which craving intensity can identify specific high‐risk populations. A mediation analysis showed that craving has a partial mediator effect on the impact of impulsivity on alcohol consumption for this population (37, 8%, P < .001). Discussion and Conclusions: The sensation seeking and lack of premeditation dimensions of impulsivity, coupled with compulsive craving, are efficient predictors of excessive alcohol consumption for university students. The partial mediator effect of craving is important in terms of characterizing the relationship between impulsivity and alcohol consumption. Scientific Significance: Our study centrally shows that the interaction between elevated levels of impulsivity and craving constitute a crucial risk factor for alcohol consumption in university students, and should thus constitute a target for primary prevention programs (Am J Addict 2019;00:00–00).